2018
DOI: 10.1038/cr.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals principles of brain retrotransposition in neurodevelopmental disorders

Abstract: Neural progenitor cells undergo somatic retrotransposition events, mainly involving L1 elements, which can be potentially deleterious. Here, we analyze the whole genomes of 20 brain samples and 80 non-brain samples, and characterized the retrotransposition landscape of patients affected by a variety of neurodevelopmental disorders including Rett syndrome, tuberous sclerosis, ataxia-telangiectasia and autism. We report that the number of retrotranspositions in brain tissues is higher than that observed in non-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 75 publications
0
61
0
Order By: Relevance
“…For instance, recent reports show that tRFs not only interfere with translation but can also affect transposon regulation and genome stability (Durdevic et al, 2013 ; Martinez et al, 2017 ; Schorn et al, 2017 ; Zhang et al, 2017 ). This activity could in principle also contribute to neurological disorders as growing evidence suggests associations between (re)expression of transposable elements and the occurrence of neuropathies (Perrat et al, 2013 ; Krug et al, 2017 ; Zahn, 2017 ; Jacob-Hirsch et al, 2018 ). In addition, beyond tRNA and tRF, the recent studies on m 6 A clearly demonstrate the involvement of mRNA modification in different aspects of neuronal development and regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, recent reports show that tRFs not only interfere with translation but can also affect transposon regulation and genome stability (Durdevic et al, 2013 ; Martinez et al, 2017 ; Schorn et al, 2017 ; Zhang et al, 2017 ). This activity could in principle also contribute to neurological disorders as growing evidence suggests associations between (re)expression of transposable elements and the occurrence of neuropathies (Perrat et al, 2013 ; Krug et al, 2017 ; Zahn, 2017 ; Jacob-Hirsch et al, 2018 ). In addition, beyond tRNA and tRF, the recent studies on m 6 A clearly demonstrate the involvement of mRNA modification in different aspects of neuronal development and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus not surprising that misregulation of m 6 A results in several physiological defects, including brain development abnormalities, obesity, cancer, and other diseases (Batista, 2017 ; Dai et al, 2018 ). In addition, the discovery of m 6 A RNA demethylases (Jia et al, 2011 ; Zheng et al, 2013 ; Jacob-Hirsch et al, 2018 ) and the identification of m 6 A-binding proteins (Dominissini et al, 2012 ) indicated that similarly to DNA modification, RNA methylation can be reversible and convey information via recognition of effector proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed earlier, Jacob-Hirsch et al (2018) showed that in autism, as well as RTT, AT, and TSC, L1Hs retrotransposition events were increased in the brains of patients with these neurodevelopmental diseases. L1Hs insertions were 8.5 fold higher in the four neurodevelopmental disorders vs. normal controls, and somatic L1Hs insertions in particular were 14.7 fold higher (Jacob-Hirsch et al, 2018). Therefore, the increases in somatic L1 activity observed in these patients might also impact ASD through inflammation or some other mechanism.…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 56%
“…Members of the L1Hs and Alu Y families are the youngest and most active RTEs in humans. The overall number of L1Hs insertions in these neurological diseases was 8.5 fold higher than the normal brain controls, and somatic L1Hs insertions in particular were 14.7 fold higher than controls (Jacob-Hirsch et al, 2018). In addition, the majority of somatic brain retrotransposition events (57%) had inserted into pre-existing repetitive elements.…”
Section: Cocaine and Methamphetamine Abusementioning
confidence: 84%
See 1 more Smart Citation